NATO and EU in conflict regulation: interlocking institutions and division of labour - Schleich, Caja (Journal of transatlantic studies, 2014)
The article examines the development of the relationship and cooperation of the European Union (EU) and North Atlantic Treaty Organization (NATO) in conflict regulation. It states that over three phases these two institutions deepened their relationship in the aspect of an intensification of their cooperation, an adoption of specific functions and a de facto clearer division of labour in conflict regulation. It will analyse whether and to what degree this cooperation and a functional division of labour is based on the functional ascription by member states or more on the activities of the institutions themselves. This comparative study will thereby contribute to a necessary theory-based analysis of the relationship of these two major international security institutions and to a deeper analysis of the inter-institutional cooperation of EU and NATO. Furthermore, it will show the importance of a combined principal- (states) and agent- (institutions) centred approach towards the shaping and explaining of inter-institutional relationships as well as going beyond the simple principal-agent relationship and advancing to the principal-agent-agent relationship.
Gesehen am 18.01.2021